Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1111/j.1468-5906.2011.01579.x
|View full text |Cite
|
Sign up to set email alerts
|

Black Churches and HIV/AIDS: Factors Influencing Congregations’ Responsiveness to Social Issues

Abstract: The ambivalent response of many black churches to current social issues has caused some scholars to question the centrality of black churches within African-American communities. Using a nationally representative sample of black congregations, this study engages the debate about the institutional centrality of black churches by focusing on their response to HIV/AIDS. Although many congregational studies treat black churches as a monolithic whole, this analysis identifies heterogeneity among black churches that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 33 publications
5
30
0
Order By: Relevance
“…Fulton (2011) argues that the timorous response of the African American church to various social problems, such as domestic abuse and substance abuse affecting the African American community, has damaged the status of the church among Black people. Given the conservative views of the African American church, it is no surprise the response to CSA has been less than desirable.…”
Section: The History Of the Black Churchmentioning
confidence: 99%
See 1 more Smart Citation
“…Fulton (2011) argues that the timorous response of the African American church to various social problems, such as domestic abuse and substance abuse affecting the African American community, has damaged the status of the church among Black people. Given the conservative views of the African American church, it is no surprise the response to CSA has been less than desirable.…”
Section: The History Of the Black Churchmentioning
confidence: 99%
“…The Black church and the Black family are the two most important institutions within the Black community (Fulton, 2011). Lincoln and Mamiya (1990) defined the Black church as the Blackcontrolled independent denominations that make up the heart of Black Christianity in the United States.…”
Section: The History Of the Black Churchmentioning
confidence: 99%
“…Further, these studies indicate that the ethnoracial composition of a congregation is not a significant predictor of service provision. Studies that focus on specific types of service-related activities reveal additional variations in participation rates across the aforementioned congregational subpopulations [3,[21][22][23][24][25].…”
Section: The Contemporary State Of Congregation-based Service Provisimentioning
confidence: 99%
“…While health activities have been increasingly documented in religious congregations, few studies have explored how HIV and other health activities are organized with respect to one another, and how other health activities may inform the development of HIV activities (or vice versa). Recent analyses found that congregations with organizational structures oriented towards community needs were significantly more likely to provide programs or activities for people living with HIV, 9,13 pointing to the importance of examining organizational facilitators. However, these studies did not explore how healthspecific organization structures affected HIV involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest that congregational decision-making processes and dynamics may be as or more important to understanding how health and HIV activities are initiated and by whom, above other oft-cited factors such as resource availability or ideological orientation. 7,13 Despite mounting evidence on the importance of health and social service activities among US congregations, there is little information on whether or how congregational HIV activities are related to other health activities. Such data on the structure and process from which HIV and other health activities emerge may be important for understanding how these activities are initiated and sustained within congregations.…”
Section: Introductionmentioning
confidence: 99%